2016
DOI: 10.1007/s00266-016-0621-1
|View full text |Cite
|
Sign up to set email alerts
|

Safe Planes for Injection Rhinoplasty: A Histological Analysis of Midline Longitudinal Sections of the Asian Nose

Abstract: This journal requires that the authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…They also found that in 14% of their cadaveric specimens, the dorsal nasal artery crossed the midline at the middle third portion of the nose. This study demonstrated that an injection perpendicular to the midline would puncture the artery in cases where the artery travels across the midline . Choi et al indicated that the dorsal nasal artery was superficial to the muscular layer at the upper (bony) portion of the nose, but beneath the fibromuscular layer at the middle (cartilaginous) portion.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…They also found that in 14% of their cadaveric specimens, the dorsal nasal artery crossed the midline at the middle third portion of the nose. This study demonstrated that an injection perpendicular to the midline would puncture the artery in cases where the artery travels across the midline . Choi et al indicated that the dorsal nasal artery was superficial to the muscular layer at the upper (bony) portion of the nose, but beneath the fibromuscular layer at the middle (cartilaginous) portion.…”
Section: Discussionmentioning
confidence: 80%
“…Smaller syringes are preferred to larger ones as a small needle necessitates slower injection and is less likely to occlude vessel . Recent studies suggest that fillers should be injected into the preperiosteal deep fatty layer, between the perichondrium/periosteum and the muscle layer, where major blood vessels are not known to be located, to avoid vascular compromise . Although many techniques have been attempted, vascular complications related to filler injection have been reported and no proven safe method has been established.…”
Section: Introductionmentioning
confidence: 99%
“…The dorsal nasal artery supplies the nose after perforating above the medial palpebral ligament at the orbit and then creates an anastomosis with the contralateral dorsal and lateral nasal arteries. Anatomical studies have shown that the dorsal nasal arteries course above the deep fatty layer and beneath the fibromuscular layer of the nose . This vessel also runs through the subcutaneous layer; thus, a superficial injection may cause vascular compromise.…”
Section: Discussionmentioning
confidence: 99%
“…20 The needle or cannula is inserted obliquely over the mid-dorsum and directed epiperiosteally in a cranial and then caudal direction, delivering 0.5 to 1.0 mL Artecoll in each direction. 21 Alternately, a 1-inch cannula is inserted parallel through a nostril, and the space of the missing bridge is filled during withdrawal. The implant is then molded with slight pressure and the patient is advised to continue using slight pressure for molding for another week if indicated.…”
Section: Underdeveloped Nasal Bridgementioning
confidence: 99%